Potential Role of Nutrient Intake and Malnutrition as Predictors of Uremic Oxidative Toxicity in Patients with End-Stage Renal Disease. (29th November 2019) - Silva, Robson E.; Simões-e-Silva, Ana C.; Miranda, Aline S.; Justino, Patrícia B. I.; Brigagão, Maísa R. P. L.; Moraes, Gabriel O. I.; Gonçalves, Reggiani V.; Novaes, Rômulo D.
Abstract : Oxidative stress is an important risk factor for cardiovascular disease and death in hemodialysis (HD) patients. However, whether biochemical and nutritional markers might be useful to stratify HD patients according to the risk of oxidative damage remains unclear. We investigated whether low-cost and easily available parameters such as the profile of nutrients intake, nutritional status, and antioxidant defenses can predict lipid and protein oxidation in HD patients. Forty-nine HD patients (women = 20, men = 29 ), ranging from 18 to 65 years of age (73.5%) were submitted to biochemical and nutritional analysis. At least 93.9% of HD patients had malnutrition. A patient's stratification according to nutritional risk was highly coherent with anthropometric parameters and nutrients intake, which were complementarily used as markers of malnutrition. Nutritional stratification was unable to reveal differences in the oxidative status. On the other hand, carbohydrate and zinc intake, serum zinc (Zn), glutathione peroxidase (GPx) activity, total antioxidant capacity (TAC), and nonprotein antioxidants (npAC) in serum were predictive markers of lipid (R 2 = 0.588, P < 0.001 ) and protein (R 2 = 0.581, P < 0.001 ) oxidation. Interestingly, GPx activity, TAC, and npAC exhibited good (> 80 % < 90 % ) or excellent (>90%) accuracy to estimate lipid oxidation (P ≤ 0.01 ). Regarding the prediction of protein oxidation, GPx activity and TAC presented regular accuracy (> 70 % < 80 % ), and Zn serum levels exhibited good sensitivity (P ≤ 0.01 ). Herein, we provided evidence that clinical characteristics relevant to predict different levels of lipid and protein oxidation in HD patients can be easily obtained, during routine hospital visits by means of the combined analyses of biochemical and nutritional parameters.